2020
DOI: 10.1007/s10637-020-00917-2
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical and radiation dose-volume factors related to pneumonitis after treatment with radiation and durvalumab in locally advanced non-small cell lung cancer

Abstract: Introduction Durvalumab has been shown to confer a survival benefit after definitive chemoradiotherapy in the patients with locally advanced non-small cell lung cancer, but no studies have attempted to identify risk factors for pneumonitis after durvalumab therapy. The purpose of this study was to investigate associations between clinical and radiation dose-volume factors, and the severity of pneumonitis. Methods We retrospectively assessed the cases of 30 patients who had been started on durvalumab therapy be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 21 publications
4
18
1
Order By: Relevance
“…In this study, the crude incidence of grade 2 or greater RP was 43%, which was consistent with reports from Asian countries 8–11,13–16 . We consider that our clinical data are comparable to reported results from other Asian facilities and could therefore validly be used for analyzing dose–volume relationships of RP and evaluating achievement degree of lung dose optimization.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In this study, the crude incidence of grade 2 or greater RP was 43%, which was consistent with reports from Asian countries 8–11,13–16 . We consider that our clinical data are comparable to reported results from other Asian facilities and could therefore validly be used for analyzing dose–volume relationships of RP and evaluating achievement degree of lung dose optimization.…”
Section: Discussionsupporting
confidence: 90%
“…However, our patient characteristics were similar to those of other retrospective studies from Japanese facilities, as were our clinical results. [8][9][10][11][13][14][15][16] Second, the cutoff values in this study reflect our early experience with lung dose optimization. More efficient lung dose optimization would further lower the target value of ratio of dose-volume parameters.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In the previous study, Inoue et al suggested that the severity of pneumonitis after durvalumab administration was not associated with V20 or any other factors [6]. However, their small-scale study was a hypothesis-generating study, and we conducted a more reliable study by adding a number of cases and events and extending the observation period; as a result, we obtained different results regarding the relationship between V20 and pneumonitis.…”
Section: Discussionmentioning
confidence: 83%